Diagnostic yield of colonoscopy in patients with colorectal symptoms from two hospitals in Malaysia - Ramasamy, Prabhu; Mat Hassan, Mohd. Zailani; Singh, Harbhajan; Singh, Manjit; Lee, Peter; Md Nor, Azmi (2010)
In Malaysia where colorectal cancer screening is not practiced, the detection of colorectal cancers and their precursors are usually in symptomatic patients. Colonoscopy is a widely available diagnostic tool for colorectal diseases. A growing demand of colonoscopic examination in medical practice has led to an inevitable rise in health care cost. Therefore, there is a need to optimize the resources for colonoscopic examination.